GIDVis: a comprehensive software tool for geometry‐independent grazing‐incidence X‐ray diffraction data analysis and pole‐figure calculations. Issue 3 (31st May 2019) - Schrode, Benedikt; Pachmajer, Stefan; Dohr, Michael; Röthel, Christian; Domke, Jari; Fritz, Torsten; Resel, Roland; Werzer, Oliver
Abstract : GIDVis is a software package based on MATLAB which is specialized for the visualization and analysis of grazing‐incidence thin‐film X‐ray diffraction data obtained during sample rotation around the surface normal. Using GIDVis, detector calibration, data stitching, intensity corrections, cuts and integrations, crystal phase analysis, and calculation of pole figures can be easily performed. Abstract : GIDVis is a software package based on MATLAB specialized for, but not limited to, the visualization and analysis of grazing‐incidence thin‐film X‐ray diffraction data obtained during sample rotation around the surface normal. GIDVis allows the user to perform detector calibration, data stitching, intensity corrections, standard data evaluation ( e.g. cuts and integrations along specific reciprocal‐space directions), crystal phase analysis etc . To take full advantage of the measured data in the case of sample rotation, pole figures can easily be calculated from the experimental data for any value of the scattering angle covered. As an example, GIDVis is applied to phase analysis and the evaluation of the epitaxial alignment of pentacenequinone crystallites on a single‐crystalline Au(111) surface.